2022
DOI: 10.1093/pcp/pcac085
|View full text |Cite
|
Sign up to set email alerts
|

Tree Peony R2R3-MYB Transcription Factor PsMYB30 Promotes Petal Blotch Formation by Activating the Transcription of the Anthocyanin Synthase Gene

Abstract: Petal blotches are commonly observed in many angiosperm families and not only influence plant-pollinator interactions but also confer high ornamental value. Tree peony (Paeonia suffruticosa Andr.) is an important cut flower worldwide, but few studies have focused on its blotch formation. In this study, anthocyanins were found to be the pigment basis for blotch formation of P. suffruticosa, and peonidin-3,5-di-O-glucoside (Pn3G5G) was the most important component of anthocyanins, while dihydroflavonol-4-reducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…And this result was consistent with the previous finding in the genus Rosa [42]. Compared with Paeonia suffruticosa cultivar 'High Noon' which had both of flavones and flavonols in petals [60] (Supplementary Table S4), Rosa 'Sunset Babylon Eyes' could directly start from the research on flavonol biosynthesis pathway. Thirdly, a variety of different carotenoids played an assisted role in the coloration of petals by adding orange or yellow hue as in other plants' flowers [29,64,65].…”
Section: A Potential Model Plant For Blotch Formation Studysupporting
confidence: 91%
See 2 more Smart Citations
“…And this result was consistent with the previous finding in the genus Rosa [42]. Compared with Paeonia suffruticosa cultivar 'High Noon' which had both of flavones and flavonols in petals [60] (Supplementary Table S4), Rosa 'Sunset Babylon Eyes' could directly start from the research on flavonol biosynthesis pathway. Thirdly, a variety of different carotenoids played an assisted role in the coloration of petals by adding orange or yellow hue as in other plants' flowers [29,64,65].…”
Section: A Potential Model Plant For Blotch Formation Studysupporting
confidence: 91%
“…However, it is difficult to know about the profile of other flavonoids and other pigments such as carotenoids (Supplementary Table S4). Even if the materials were used with different colors in both blotch and non-blotch parts, there were still few reports comparing anthocyanins, flavones and flavonols, as well as carotenoids at the same time between these two parts [60][61][62][63] (Supplementary Table S4). In this study, the flavonoids and carotenoids were identified and characterized together in a Rosa Hulthemia hybrid 'Sunset Babylon Eyes' with rose-red to dark red blotch and yellow nonblotch parts.…”
Section: A Potential Model Plant For Blotch Formation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In Vaccinium myrtillus , two MYBA‐type genes, VmMYBA1 and VmMYBA2 , were revealed to regulate anthocyanin biosynthesis in berries and vegetative tissues, while MYBPA1‐type TF was found to promote anthocyanin biosynthesis during berry ripening by directly activating enzyme genes (Karppinen et al, 2021). In Paeonia suffruticosa , PsMYB30 regulates anthocyanin biosynthesis by activating the expression of the PsANS gene to promote petal blotch formation (Luan et al, 2022). In this study, six MYB genes ( RgMYB41 , RgMYB42 , RgMYB43 , RcMYB1 , RcMYB3 , and RhMYB1 ) were cloned from R. glutinosa , R. chingii , and R. henry .…”
Section: Discussionmentioning
confidence: 99%
“…Except for avonols, there are luteolin glycosides detected in Michelia crassipes [51]. Luteolin and chrysoeriol glycosides had been found in petals of tree peony besides avonols [52]. In both of the blotch and the non-blotch parts, avonols (quercetin glycosides and kaempferol glycosides) existed in petals of 'Sunset Babylon Eyes' at the same time.…”
Section: Flavonols Act As Background Color In Petals Of 'Sunset Babyl...mentioning
confidence: 96%